Technologies To Fully Generate A Synthetic Training Experience - Keith Brawner; Roy Wall (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
There are a variety of technologies needed to create a fully synthetic training experience from the “bottom up” (ie. “a fully created synthetic experience”) and from the “top down” (ie. created for the user who needs training). This paper outlines the technologies required with the note that many of them currently exist in research form; it describes the world soon to come to computer aided instruction.